A Story of Conquest and Adventure The Large Farāmarznāme - van Zutphen, Marjolijn (Iranian Studies Series, 2017)
The Large Farāmarznāme (Farāmarznāme-ye bozorg), a poem from the Persian epic cycle dated to the late eleventh century, is hereby published for the first time in an English translation, in prose. The story tells how Farāmarz, a son of the famous Shāhnāme hero Rostam, conquers several provinces of India, before setting off on an extensive voyage over sea and land, leading his troops through a number of hazardous situations in various fictional countries. As a true epic hero, he displays his prowess in battle and in single combat against men, demons and various ferocious animals, in addition to experiencing a number of marvelous and romantic adventures.This critical edition contributes to our understanding of post-Firdawsian Persian epic. The translation of this work into a Western language is therefore an invaluable source of reference for further scholarship.